Free market for all / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The objectives of the programme were to create a platform in nurturing charitable attitude among the students and lecturers by donating goods or ser-vices to those in need, to build a good relationship between UiTM and the public community, and to establish communities that complement each oth-er. Although it was held for the first time, it surprised the organizer as the programme had attracted 300 participations.